2022
DOI: 10.3390/fib10080067
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Maximum Strain for Different Steel-FRCM Systems in RC Beams Strengthened in Flexure

Abstract: The strengthening of existing reinforced concrete (RC) structures by means of steel-fabric reinforced cementitious matrix (Steel-FRCM) systems has been universally recognized in the academic literature as an effective method. Several types of steel fibres can be found in the marketplace, and they are classified according to mass per unit area and tensile strength. In the flexural strengthening design of RC beams, a fundamental parameter is the effective tensile strain level in the Steel-FRCM system attained at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Ebead et al (2019) observed that RC beams strengthened using one or two layers of PBO fabric failed to fabric slippage whereas, failed due to delamination of layers when three layers of strengthening were adopted. This similar phenomenon was also observed by Elsanadedy et al (2013); Bencardino and Nisticò (2022). Besides Elsanadedy et al (2013) also compared the ductility response of FRP and TRM (basalt-based textile) strengthened RC beams wherein the ductility of TRM strengthened beam was found to be superior to the FRP strengthened beam.…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations
“…Ebead et al (2019) observed that RC beams strengthened using one or two layers of PBO fabric failed to fabric slippage whereas, failed due to delamination of layers when three layers of strengthening were adopted. This similar phenomenon was also observed by Elsanadedy et al (2013); Bencardino and Nisticò (2022). Besides Elsanadedy et al (2013) also compared the ductility response of FRP and TRM (basalt-based textile) strengthened RC beams wherein the ductility of TRM strengthened beam was found to be superior to the FRP strengthened beam.…”
Section: Introductionsupporting
confidence: 76%
“…In international literature, there are a substantial amount of research articles on the strengthening effect of TRM in reinforced concrete (RC) beams (Loreto et al, 2015;Qaidi et al, 2022a;Bencardino and Nisticò, 2022). Loreto et al (2015) evaluated the performance of RC beams strengthened using Fabric reinforced cementitious matrix (FRCM) in shear zone in the form of U-wraps.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, industries such as automotive, aerospace, architecture and marine are continuously exploring the potential of this material [6,7]. In civil engineering, fibre-reinforced polymer composites (FRPs) are used in reinforcing bars, sandwich panels and structural retrofitting [8,9]. However, due to the organic nature of the matrix, FRPs are impermeable to vapour, they are flammable and their application on a wet surface at low temperatures is not readily achievable.…”
Section: Introductionmentioning
confidence: 99%